Spatial effects of open borders on the Czech labour market - Michael Moritz (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2008)
Hardly noticed in Western Europe the fall of the Iron Curtain had also ef-fects on the regional structures of the labour markets in the Central and Eastern Euro-pean Countries (CEEC). I analyse whether during the undoubtedly increasing integration of markets the Czech border region close to the Western European high-wage countries benefited from its geographical position. Even without transnational free labour mobility, free trade and outsourcing of production activities can lead to shifts in the labour demand and wage structure with respect to different skill groups. These integration effects should be stronger in border regions. Using data from the Czech Microcensus and quarterly dis-trict level data, I investigate the impact of the fall of the Iron Curtain on the regional differ-ences in unemployment, the skill structure of employment and wages in the Czech Re-public. According to my results there are no indications of disproportionate shifts in the economic structure as well as in the skill structure in the Czech districts neighbouring Bavaria and Austria compared to non-border districts. However, regarding wage differ-entials between workers employed in the border region and workers in the rest of the country, I find evidence that between 1996 and 2002 the border region workers of the lowest skill category exhibit a positive wage differential of around 12% compared to their counterparts in non-border districts. For all other skill groups in the border region the spatial wage gap is negative and, in absolute value, increases with the skill level. – – Der Beitrag untersucht, ob die tschechische Grenzregion in unmittelbarer Nähe zu den westeuropäischen Hochlohnländern während der zunehmen-den Integration der Märkte von ihrer geographischen Lage profitierte. Auf der Basis von Daten des tschechischen Mikrozensus und vierteljährlicher aggregierter Daten auf Kreis-ebene werden die Auswirkungen des Falls des Eisernen Vorhangs auf regionale Unter-schiede bezüglich Arbeitslosigkeit sowie Qualifikations- und Lohnstruktur in der Tsche-chischen Republik analysiert. Die Ergebnisse zeigen, dass es keine Hinweise auf über-proportionale Veränderungen in der Wirtschafts- und Qualifikationsstruktur in den an Bayern und Österreich angrenzenden tschechischen Kreisen im Vergleich zu den nicht im Grenzgebiet liegenden Bezirken gab. Wenn man die Lohnunterschiede zwischen Ar-beitnehmern in der Grenzregion und Arbeitnehmern im Rest des Landes betrachtet, zeigt sich, dass zwischen 1996 und 2002 die Beschäftigten in der Grenzregion mit der niedrigsten Qualifikationsstufe einen positiven Lohnunterschied von rund 12 Prozent im Vergleich zu entsprechenden Beschäftigten im Binnenland aufweisen. Für alle anderen Qualifikationsgruppen in der Grenzregion ist die räumliche Lohnkluft negativ und nimmt in absoluten Zahlen mit ansteigender Qualifikation zu.
Keywords: J24; J31; F16; 330; regional labour markets; border regions; international trade; employment; wage inequality; Regionaler Arbeitsmarkt; Grenzgebiet; Standortfaktor; Beschäftigungseffekt; Lohnniveau; Qualifikation; Tschechische Republik